Effects of Long-Term Mowing on Biomass Composition in Pannonian Dry Grasslands - Judit Házi; Károly Penksza; András Barczi; Szilárd Szentes; Gergely Pápay (Agronomy, 2022)
This study is focused on the vegetation of seminatural dry grasslands. These grasslands are valuable with large biodiversity; however, their long-term preservation requires regular conservation management. This report demonstrates the results of a 13-years mowing experiment, designed to suppress the spread of an unpalatable grass species, Calamagrostis epigejos. The study site was located in mid-successional grasslands, in the Western-Cserhát, near Rád, Northern Hungary. The experimental design consisted of eight permanent plots, where mowing was applied twice a year. The vegetation was sampled annually (from 2001 to 2013). The impacts of mowing were tested using repeated–measures analyses of variance (ANOVA). In 2001, Calamagrostis epigejos was the species with the highest cover in both the mown and control sites, with an average cover value of 63%. However, as a result of mowing, a significant difference was detected in the amount of litter and legumes species as well. The number of species showed an increase in both types of treatment, from 15 to 37 in the mowed plots, but also from 18 to 27 in the control plots. We concluded that mowing twice a year proved to be a useful measure for modifying botanical composition of a grassland. It was well suited for agricultural usage, in particular grazing, which can replace the expensive and time-consuming scythe. Mowing can also be a suitable management measure for controlling native invader species such as Calamagrostis epigejos, and can significantly increase the proportion of species with higher forage values.